Jus ad bellum series: self-defence against armed non-state actors in the MENA region - Nessa, Jasmin Johurun; Kleczkowska, Agata (Journal on the use of force and international law, 2024)
This article marks the launch of the new 'Jus ad bellum Series' in the Journal on the Use of Force and International Law, designed to explore the evolving state practice in the jus ad bellum regime. This inaugural piece explores the evolving state practice in relation to self-defence against armed non-state actors (ANSAs), focusing specifically on the Middle East and North Africa (MENA) region. The article is structured into four key sections: first, the interpretation of Article 51 of the UN Charter; second, the contentious issue of anticipatory self-defence, focusing on how recent state practice has reshaped the concept of imminence in response to modern security threats; third, the criteria of necessity and proportionality; finally, the 'unwilling or unable' doctrine. The analysis of Article 51's interpretation reveals significant variation in how states frame their self-defence claims, reflecting the complexity of applying traditional jus ad bellum rules to contemporary security threats.